Higher Muscle Damage Triggered by Shorter Inter-Set Rest Periods in Volume-Equated Resistance Exercise - Senna, Gilmar Weber; Dantas, Estélio Henrique Martin; Scudese, Estevão; Brandão, Paula Paraguassú; Lira, Vitor A.; Baffi, Matheus; Ribeiro, Luiz Claudio Pereira; Simão, Roberto; Thomas, Ewan; Bianco, Antonino (Frontiers in Physiology, 2022)
Objectives The aim of the manuscript was to analyze the effects of two rest periods between volume-equated resistance exercise (RE) on inflammatory responses (cytokines and leukocyte) and muscle damage. Methods Ten trained men (26.40 ± 4.73 years, 80.71 ± 8.95 kg, and 176.03 ± 6.11 cm) voluntarily participated in training sessions consisting of five sets of 10 reps performed at 10-RM on (1) the barbell bench press followed by (2) leg press, with either 1- or 3-min rest between sets and exercises. Circulating concentrations of different biomarkers was measured before (Pre), and after 3 h (excepted for cytokines), 6, 12, and 24 h from exercise. The rate of perceived exertion (RPE) was recorded after each set on both planned visits. Results We found greater increases triggered by the 1-min rest period in Creatine Kinase (CK), occurring from 12 to 24 h post-exercise compared to the 3-min rest condition. A significant increase in the 1-min rest condition was also observed in the total number of leukocytes, neutrophils, and monocytes. The 1-min rest period also triggered increases compared to baseline in pro-inflammatory cytokines [Interleukin 1 beta (IL-1β), p = 0.004; tumor necrosis factor α (TNF-α), p = 0.01; and granulocyte-macrophage colony-stimulating factor (GM-CSF), p = 0.01], which were more evident after 6 and 12 h post-exercise. Similarly, increases in anti-inflammatory cytokines [Interleukin 5 (IL-5), p = 0.01; Interleukin 6 (IL-6), p = 0.01; and Interleukin 10 (IL-10), p = 0.01] at all time-points were observed. Conclusion Our results indicate that a 1-min rest condition in volume-equated RE promoted greater overall muscle tissue damage with a longer duration of the inflammatory processes compared to a 3-min rest.